Education, human capital development and Malaysia's economic transformation: Issues & challenges - Jaafar, Ahmad Sobri; Abdullah, Muhammad Ridhuan Bos (2007)
Malaysia’s vision is to become a developed nation by the year 2020. Central to the fulfillment of this vision is enhancing the productivity and competitiveness of the country. This will involve both moving up the value chain into higher value-added industrialization and services, and developing new areas of competitive advantages. A major precondition for competitiveness is the availability of skilled workforce through the provision of education and training. The objective of this paper is to highlight some of the issues and challenges on education and human capital development face by Malaysia in her efforts to sustain her competitive advantage and fulfilling her development vision. Malaysia’s educational level and system are no doubt among the best in the developing countries. However, there are still some shortcomings and rooms for further improvements. To move to higher value-added industrialization and services and become competitive requires a good education foundation and a 'learning society'.